Use of active transport to increase the quality of life of the urban population during the covid-19 pandemic in the light of a bibliometric approach - Abreu, Victor Hugo Souza de; Almeida, Isabella Martins de; Turini, Larissa Rodrigues (Brazilian Journal of Production Engineering, 2021)
The restrictions implemented by governments to curb the spread of the coronavirus (COVID-19), including social distance, isolation and home confinement, had a major impact on the quality of life of the urban population. Thus, the use of active transportation started to be configured as an important strategy so that the population had access to essential goods, allowing a greater distance between individuals, as well as to improve aspects related to physical and mental health, during the period pandemic. Serving this purpose, this article aims to carry out a bibliographic review with a bibliometric approach to identify how active transportation can positively influence the quality of life of the urban population during the pandemic period. The results indicate that research on the subject, although premature, is growing, and studies have been published in important international journals. In addition, the discussions raised here show that active transportation corresponds to a critical mode that deserves more attention and funding, both during normal periods and in major social disruptions, such as a pandemic such as COVID-19.
Keywords: COVID-19; Transporte activo; Análisis bibliométrico